The analysis of the use a combination of metformin and glibenclamide drugs with blood glucose levels at diabetes mellitus patients - Mayasari, Shinta (Sean Institute, 2024)
Diabetes mellitus is a non-communicable disease which is a concern a national and global public health problem. Indonesia was ranks sixth in the world with a prevalence of 8,6% of the total population and it is estimated that in 2025 it will increase to 12,4 million sufferers. This research was conducted at the one of public health center. The purpose of this study was to determine changes at blood glucose levels of diabetes mellitus patients on administration of a combination of metformin and glibenclamide drugs. This research used a type of comparative, comparatively paired sample analytical research, with the design cohort retrospective. The instrument used in this research was a patient's medical record. The population in this study were all adults diabetes mellitus patients that over 18 years old at the period of March-Mei 2020.Samples were calculated using the total sampling technique during the research period. The Data was processed using SPSS version 18 and analyzed use Wilcoxon test.The results showed that random blood glucose levels before the use of a combination metformin and glibenclamide with an average of 292,80 mg/dl and after using combination metformin and glibenclamide drugs was had decrease of -76.1mg/dl. Conclusion: A combination of metformin and glibenclamide drugs provided changes in blood glucose levels decrease in diabetes mellitus patients, so it can be used as an antihyperglycemic recommendation according to the classification of patients in research.